Preparation method of nickel cluster loaded-porous metal organic framework material for efficient photocatalytic reduction of CO2

The problem of low photoreduction efficiency of CO2 is solved by loading nickel clusters onto ZIF-8 material, and efficient and stable photocatalytic carbon dioxide reduction is achieved, which improves CO2 adsorption and activation capabilities, inhibits water reduction and hydrogen evolution reaction, and significantly improves the Photocatalytic activity and carbon monoxide generation efficiency are obtained.

CN119140165AInactive Publication Date: 2024-12-17EAST CHINA UNIV OF SCI & TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411281201.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2024-12-17
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The efficiency of selective carbon monoxide generation of photocatalytic reduction of carbon dioxide is low, mainly because CO2 molecules are difficult to be activated and reduced, and the competition for water reduction hydrogen evolution reaction in the aqueous phase system is strong, resulting in low CO2 photoreduction efficiency.

Method used

Nickel cluster loading on porous metal organic frame material ZIF-8 is used to prepare nickel cluster-loaded porous metal organic frame material by sodium borohydride reduction method, providing active sites and electron capture sites to enhance CO2 adsorption and activation. And the visible light absorption and photogenerated charge mobility are improved through metal nickel modification, and the water reduction hydrogen evolution reaction is suppressed.

Benefits of technology

It achieves efficient and highly stable photocatalytic carbon dioxide reduction under mild conditions, significantly improves the activity and selectivity of CO2 photoreduction reaction, improves the utilization rate of light energy, and reduces the energy consumption and greenhouse gas emissions of traditional catalysts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

The invention provides the preparation method of the material with the performance of photocatalytic reduction of carbon dioxide (CO2), the material can selectively convert carbon dioxide into carbon monoxide (CO) under mild conditions, and a raw material is provided for preparation of chemicals with higher value. According to the invention, nickel chloride hexahydrate (NiCl2. 6H2O), zinc nitrate hexahydrate (Zn (NO3) 26H2O) and dimethylimidazole (C4H6N2) are respectively used as a nickel source and a zinc source, an acetonitrile solution (MeCN) of sodium borohydride (NaBH4) is used as a reducing agent, and the nickel cluster loaded porous metal organic framework (Ni-ZIF-8) material can be prepared through a NaBH4 reduction treatment method. According to the method disclosed by the invention, the loading capacity of nickel can be simply controlled by controlling the input NiCl2. 6H2O, and the Ni cluster fixed on the ZIF-8 can be used for reducing the reaction potential barrier in the CO2 photoreduction process and inhibiting the competition of hydrogen evolution reaction (HER) at the same time, so that the activity of the CO2 photoreduction reaction is favorably improved. Compared with unmodified ZIF-8, the Ni-ZIF-8 material has higher visible light absorptivity, carbon dioxide molecule activation capacity and charge separation efficiency, shows excellent activity, selectivity and stability for synthesizing carbon monoxide (CO) through photocatalytic conversion of CO2 under the illumination condition, realizes the CO yield of 15.02 mmol g <-1 > h <-1 >, and has electron selectivity of 94%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a nickel cluster-loaded porous metal organic framework material for selectively generating carbon monoxide by photocatalytic reduction of carbon dioxide, belonging to the field of nanomaterials and photocatalytic technology. Background Art

[0002] Using solar energy to convert CO2 into high value-added compounds such as CO, CH4 and HCOOH is one of the most promising carbon cycle pathways that can simultaneously alleviate the greenhouse effect and energy crisis. However, the selective generation of CO by photocatalytic reduction of CO2 remains a huge challenge. On the one hand, due to the extremely stable chemical bond of CO2 molecules (C=O, 750kJ mol -1 ) makes CO2 difficult to be activated and reduced. In addition, another important reason for the low efficiency of photocatalytic CO2 reduction is the competitive reaction of water reduction hydrogen evolution (HER) in the aqueous system. Therefore, enhancing the adsorption and activation of CO2 molecules on the catalyst surface during CO2 photoreduction is a feasible method to inhibit the HER reaction while improving the activity and selectivity of CO2 photoreduction. Imidazole metal organic frameworks (MOFs) ZIF-8 is a typical porous material that has attracted widespread attention due to its excellent ability to capture CO2 molecules. The micropores of ZIF-8, as a molecular reaction chamber, can effectively capture and imprison CO2 molecules, but lack active sites for activating and reducing CO2 molecules. Nickel has always performed well in the carbon dioxide reduction reaction. Nickel clusters can improve the activity and selectivity of CO2 photoreduction by increasing the H + The adsorption energy barrier on the catalyst surface inhibits the HER reaction and reduces the reaction energy barrier in the CO2 photoreduction process. Modifying semiconductors with nickel clusters can increase the mobility of photogenerated charges and improve photocatalytic activity. At present, metal cluster-modified MOFs photocatalysts have not been widely used in the photocatalytic reduction of CO2, and the reaction mechanism induced by metal clusters needs to be explored.

[0003] Therefore, based on the above research background, from the effective adsorption of CO2 and the efficient separation of photogenerated charges, the present invention prepares nickel cluster-loaded porous metal organic framework materials, and systematically compares the material with porous metal organic framework materials modified by other metals and unmodified ZIF-8 materials. On the one hand, the nickel clusters loaded on ZIF-8 can provide a large number of active sites and electron capture sites, which are conducive to the adsorption and activation of CO2. On the other hand, metallic nickel can increase the absorption of visible light by ZIF-8 materials, and porous materials help to strengthen the interaction between light and matter through the slow light effect, thereby improving the utilization of light energy. At the same time, the Ni-modified ZIF-8 porous material can effectively promote the separation and migration of photogenerated carriers, thereby improving the photocatalytic activity. The porous metal organic framework material loaded with nickel clusters prepared by the present invention realizes efficient and highly stable photocatalytic carbon dioxide reduction under mild conditions. Summary of the invention

[0004] The present invention adopts sodium borohydride reduction method to load nickel in the form of clusters onto ZIF-8 multi-level porous material, firstly prepares ZIF-8 as a carrier by hydrothermal method, and then immerses it in metal precursor solution. After sodium borohydride reduction, a porous metal organic framework material loaded with nickel clusters can be obtained.

[0005] Zn(NO3)2·6H2O (1.116 g) was dissolved in CH3OH (30 mL) solution and ultrasonically treated for 3 min to form solution A. Dimethylimidazole (1.232 g) was then dissolved in CH3OH (30 mL) solution and ultrasonically treated for 3 min to form solution B. Solutions A and B were then mixed and ultrasonically treated for 10 min, and the mixed solution was poured into a 100 mL polytetrafluoroethylene reactor, and then reacted in a 120°C constant temperature oven for 2 h. After natural cooling, the catalyst at the bottom of the reactor was centrifugally washed with CH3OH three times to obtain a white powder. The obtained white powder was then placed in a vacuum oven at 60°C and dried overnight, and the final powder obtained was ZIF-8.

[0006] The method for constructing a porous metal organic framework material loaded with nickel clusters according to the present invention is as follows: 0.1g ZIF-8 is dissolved in 35mL acetonitrile, ultrasonically treated for 5min, and then 5mL of NiCl2·6H2O (4mg, 5mL) acetonitrile solution is added to the suspension and stirred for 30min. Then, an acetonitrile solution of NaBH4 (6.8mg, 10mL) is dripped into the mixed solution. In order to complete the reaction, stirring is continued for 20min until no bubbles are generated. The precipitate is collected by centrifugation and washed with acetonitrile for multiple times. Finally, the product Ni-ZIF-8 is obtained by vacuum drying in an oven at room temperature. In a similar manner, the amounts of NiCl2·6H2O and NaBH4 added during the reaction are adjusted in proportion to prepare 0.5Ni-ZIF-8 and 2Ni-ZIF-8 samples.

[0007] The method for preparing metal organic framework materials loaded with different metal elements involved in the present invention is as follows: metal organic framework materials loaded with other elements are prepared according to the nickel loading method, and nickel chloride hexahydrate is replaced with ferric chloride hexahydrate, cupric chloride dihydrate, cobalt chloride hexahydrate, and nickel nitrate hexahydrate respectively.

[0008] The advantages of the present invention are embodied in

[0009] 1. Using ZIF-8 as a photocatalytic semiconductor can effectively capture and confine CO2 molecules, solving the problem of low probability of CO2 molecules contacting the catalyst due to their low solubility in water, enhancing the adsorption of CO2 molecules on the catalyst surface during CO2 photoreduction, realizing the conversion of carbon dioxide under mild conditions, and solving the problem of high energy consumption and increased greenhouse gas emissions in traditional catalysis.

[0010] 2. Ni is loaded onto ZIF8 in the form of clusters. Ni clusters serve as active sites and electron capture sites, which are beneficial to the adsorption and activation of CO2. Ni clusters improve the activity of CO2 photoreduction reaction by reducing the reaction barrier in the CO2 photoreduction process and inhibiting the HER reaction.

[0011] 3. Metallic nickel can increase the absorption of visible light by ZIF-8 materials. The porous material helps to strengthen the interaction between light and matter through the slow light effect, thereby improving the utilization of light energy. At the same time, the Ni-modified ZIF-8 porous material can effectively promote the separation and migration of photogenerated carriers, thereby improving the photocatalytic activity. The synergistic effect of clustered nickel and porous metal organic framework materials improves the absorption and utilization of light energy, solving the disadvantage of low charge utilization of photocatalysts. BRIEF DESCRIPTION OF THE DRAWINGS

[0012] Figure 1a is a scanning electron microscope (SEM) image of ZIF-8 in Example 1, and it is observed that ZIF-8 has a typical regular dodecahedral structure. Figure 1 b and Figure 1 c are the high-angle annular dark field scanning transmission electron microscopy (HAADF-STEM) images of Ni-ZIF-8 in Example 2 and Ni / ZIF-8 (SAs) in Example 3, respectively. It can be observed that the morphology of Ni / ZIF-8 and Ni / ZIF-8 (SAs) is still a regular dodecahedral structure, which indicates that the loading of nickel clusters will not cause the collapse of the ZIF-8 structure. Figure 1 d and Figure 1 e is a transmission electron microscope (TEM) image of the Ni-ZIF-8 sample in Example 2, from which it can be clearly seen that Ni is enriched on the surface of ZIF8 in the form of small clusters. In order to determine the crystal structure of different catalysts, powder X-ray diffraction (XRD) characterization was performed. Figure 1 f is the XRD spectrum of M-ZIF-8 (M = Ni, Fe, Cu and Co), Ni / ZIF-8 (SAs) and ZIF-8. The catalysts all have highly uniform characteristic peaks, and no obvious characteristic peaks of transition metals are observed in the spectrum, confirming that Ni is highly dispersed on ZIF-8.

[0013] Figure 2 a is the N2 adsorption-desorption curve of Ni-ZIF-8 in Example 2 and its pore size distribution. Combined with the BET specific surface area measurement data, it can be seen that the specific surface area of ​​the samples is reduced after the introduction of Ni, and the specific surface area is significantly reduced after the introduction of Ni single atoms, which verifies the previously proposed conjecture: the Ni single atoms introduced in situ replace part of the Zn in ZIF-8, and the Ni single atoms are uniformly distributed throughout the ZIF-8, resulting in a significant reduction in specific surface area. In order to prove the advantage of Ni clusters in CO2 molecular adsorption, ZIF-8, Ni-ZIF-8 and Ni-ZIF-8 (SAs) were characterized by CO2 gas temperature rise desorption (CO2-TPD). Figure 2 b is the CO2 gas heating desorption diagram of different samples. Compared with ZIF-8, Ni-ZIF-8 exhibits better CO2 molecule adsorption capacity, indicating that nickel clusters can serve as good adsorption sites for CO2 molecules.

[0014] Figure 3a is the photocatalytic CO2 reduction performance diagram of ZIF-8, Ni-ZIF-8(SAs), x-Ni / ZIF-8, Fe-ZIF-8, Cu-ZIF-8 and Co-ZIF-8. Compared with ZIF-8, the production of CO products in the photocatalytic CO2 reduction process of Ni-ZIF-8(SAs) increased significantly, but the production of H2 did not increase, indicating that the loading of Ni single atoms promoted the production of CO in the photocatalytic CO2 reduction process, but had no promoting effect on the production of H2. The Ni-ZIF-8 photocatalyst formed by the loading of nickel clusters on ZIF-8 showed the best CO2 reduction ability, with a CO production of 18.314mmol g in 3h. -1 , which are 18 times and 9 times that of ZIF-8 and Ni-ZIF-8(SAs) respectively under the same test conditions. At the same time, Co-ZIF-8 significantly improved the photocatalytic CO2 reduction performance relative to the catalyst without cluster loading, but did not show obvious selectivity for CO2 photoreduction or HER reaction. Cu-ZIF-8 showed high selectivity for HER reaction among the three metal cluster-loaded catalysts, indicating that the metal cluster species have significant differences in the products. After analyzing the photocatalytic performance of different catalysts, it can be reasonably speculated that Ni clusters act as active sites in the photocatalytic process, significantly affecting the adsorption and activation of CO2 molecules on the catalyst surface, and promoting the generation of CO products. Figure 3 b is the product yield diagram of Ni-ZIF-8 photocatalyst accumulated over time. From the bar graph, it can be observed that the production of CO gradually increases, while the production of H2 does not increase with the extension of , which further proves that Ni-ZIF-8 catalyst will inhibit the occurrence of HER reaction. In order to further explore the photocatalytic CO2 reduction process, the product yield change was measured every 0.5h. Figure 3 c is the CO2 reduction activity diagram of Ni-ZIF-8. The lowest yield was observed in the first 0.5 h, which may be due to the activation process of the catalyst, resulting in poor initial performance. Subsequently, the catalytic performance first increased and then gradually decayed. There are two possible explanations: (1) the Ni-ZIF-8 photocatalyst deactivated over time or (2) the photosensitization phenomenon of the photosensitizer caused the photosensitizer to deactivate. In order to determine the cause of the performance decline, additional photosensitizer was added in the fourth hour. The catalyst performance 0.5 h after the addition of the photosensitizer returned to the highest point, indicating that the Ni-ZIF-8 photocatalyst was not deactivated. The performance decline was due to the photosensitization effect of the photosensitizer, further proving the excellent stability of the Ni-ZIF-8 photocatalyst. Finally, in order to ensure the credibility and authenticity of the experimental results, it is necessary to confirm the source of the carbon element in the carbon-containing product, so a single variable comparison experiment was carried out. Figure 3d is the activity diagram of Ni-ZIF-8 under different conditions. After removing the hole trap (TEOA) from the photocatalytic CO2 reduction system, the photocatalytic activity decreased significantly, because the presence of TEOA would capture photogenerated holes, thereby reducing the recombination rate of photogenerated carriers and increasing the utilization rate of photogenerated electrons. When TEOA was removed, the electron utilization rate decreased, resulting in a decrease in the activity of photocatalytic CO2 reduction. In addition, no products were detected after removing the catalyst or light source from the photocatalytic CO2 reduction system, indicating that Ni-ZIF-8 is the only effective photocatalyst in the catalytic system and light driving is a necessary condition. There was almost no product after removing the Ru photosensitizer, indicating that the photogenerated electrons came from Ru photosensitization. After replacing CO2 gas with Ar in the catalytic process of photocatalytic CO2 reduction, only the presence of H2 was detected, indicating that the carbon element in the CO product came from CO2 molecules rather than other carbon sources.

[0015] Figure 4 a is the XPS graph of different samples. The 2p orbitals of Zn in different samples 1 / 2 and 2p 3 / 2 The characteristic peaks showed no signs of electron migration at different loading levels. Figure 4 b is the XPS spectrum of Ni 2p of the Ni-ZIF-8 sample in Example 2. 1 / 2 and Ni 2p 3 / 2 The binding energy peaks are located at 855.68eV and 872.59eV, respectively, which indicates that Ni is between the zero-valent and oxidized states. Figure 4 c is the XPS spectrum of Ni 2p of the Ni-ZIF-8(SAs) sample in Example 2. Figure 4 d is the electrochemical impedance diagram of different samples. The Ni-ZIF-8 sample shows a lower electrochemical impedance, which means that the nickel clusters reduce the material electron transfer barrier and help improve the photogenerated carrier mobility. Figure 4 e is the room temperature fluorescence emission spectra of different catalysts. The main fluorescence emission peak intensity of Ni-ZIF-8 at 470nm is greatly reduced, indicating that the recombination of electron-hole pairs in the MOFs catalyst itself is suppressed. Figure 4 f is the UV-visible diffuse reflectance spectrum of different catalysts. After loading metal, the absorption range of ZIF8 has changed to varying degrees. The visible light absorption of ZIF8 with different Ni loading increases with the increase of Ni loading, which is beneficial to the absorption and utilization of light energy by the catalyst. Among them, the absorption range of highly dispersed Ni-ZIF8 is greater than that of single-atom Ni-ZIF8, indicating that metal co-catalysts in a highly dispersed state are more conducive to the absorption of light energy by the catalyst. Figure 2 and Figure 4The results show that Ni cluster-loaded samples can enhance visible light absorption, promote the separation and migration of photogenerated charges, and thus improve the photocatalytic CO2 reduction performance.

[0016] Figure 5 a is the in-situ FTIR image of ZIF-8, Figure 5 b and Figure 5 c is the in-situ FTIR image of Ni-ZIF-8. Figure 5 As shown in b, about 1455cm -1 The vibration peak at comes from HCO 3- The group is formed by the reaction of CO2 with hydroxyl groups in the solvent. 1370 and 1292 cm -1 The absorption peak at corresponds to the monodentate carbonate (m-CO3 2- ) and CO2 molecules adsorbed on the surface (*CO2). The 1570 and 1623 cm -1 The characteristic peaks at ≈1933 and ≈2083 cm -1 The two characteristic peaks correspond to the *CO intermediate, further proving that Ni-ZIF-8 has good CO generation performance. Based on in situ FTIR spectroscopy analysis, the photocatalytic CO2 reduction process on highly dispersed Ni sites is as follows: First, CO2 molecules adsorb on highly dispersed Ni sites to form Ni-COO intermediates (shown in Equation 1-1). Under light excitation, photogenerated electrons and protons are transferred to the Ni-COO intermediate to generate Ni-COOH intermediates (shown in Equation 1-2). Ni-CO intermediates are formed by the dehydration reaction of Ni-COOH (shown in Equation 1-3). Finally, *CO desorbs from the Ni active site, releasing CO gas, and the Ni-ZIF-8 photocatalyst returns to the original state of the photocatalyst, re-exposing the active site (shown in Equation 1-4).

[0017] CO2 (g) + * → *CO2 (1-1)

[0018] *CO2 + e - + H + → *COOH (1-2)

[0019] *COOH + e - + H + → *CO+H2O (1-3)

[0020] *CO → * + CO (g) (1-4)

[0021] The above experimental results prove that the nickel cluster-loaded porous metal-organic framework material we synthesized has excellent photocatalytic CO2 reduction performance and stability.

[0022] Although the present invention has been described in detail through the above preferred embodiments, it should be appreciated that the above description should not be considered as limiting the present invention. Specific implementation plan

[0023] The present invention will be described in more detail below through specific embodiments, but the protection scope of the present invention is not limited to these embodiments.

[0024] Example 1

[0025] Synthesis of ZIF-8

[0026] Zn(NO3)2·6H2O (1.116 g) was dissolved in CH3OH (30 mL) solution and ultrasonically treated for 3 min to form solution A. Dimethylimidazole (1.232 g) was then dissolved in CH3OH (30 mL) solution and ultrasonically treated for 3 min to form solution B. Solutions A and B were then mixed and ultrasonically treated for 10 min, and the mixed solution was poured into a 100 mL polytetrafluoroethylene reactor, and then reacted in a 120°C constant temperature oven for 2 h. After natural cooling, the catalyst at the bottom of the reactor was centrifugally washed with CH3OH three times to obtain a white powder. The obtained white powder was then placed in a vacuum oven at 60°C and dried overnight, and the final powder obtained was ZIF-8.

[0027] Example 2

[0028] Synthesis of Nickel Cluster-loaded Porous Metal-Organic Framework (Ni-ZIF-8) Materials

[0029] 0.1g ZIF-8 was dissolved in 35mL acetonitrile and ultrasonically treated for 5min. Then 5mL of NiCl2·6H2O (4mg, 5mL) in acetonitrile solution was added to the suspension and stirred for 30min. Then NaBH4 in acetonitrile solution (6.8mg, 10mL) was added dropwise to the mixed solution. In order to complete the reaction, stirring was continued for 20min until no bubbles were generated. The precipitate was collected by centrifugation and washed with acetonitrile several times. Finally, it was dried in a vacuum oven at room temperature to obtain the finished Ni-ZIF-8. In a similar way, the amount of NiCl2·6H2O and NaBH4 added during the reaction was adjusted in proportion to prepare 0.5Ni-ZIF-8 and 2Ni-ZIF-8 samples.

[0030] Comparative Example 1

[0031] Synthesis of single-atom nickel-supported porous metal-organic framework (Ni-ZIF-8SAs) materials

[0032] First, Zn(NO3)2·6H2O (1.116 g) and an appropriate amount of Ni(NO3)2·6H2O were dissolved in a CH3OH (30 mL) solution to form solution A. Then, dimethylimidazole (1.232 g) was dissolved in a CH3OH (30 mL) solution to form solution B. Then, solutions A and B were mixed and ultrasonically treated for 10 min, and the mixed solution was poured into a 100 mL polytetrafluoroethylene reactor, and then reacted in a blast constant temperature oven at 120 ° C for 2 h. After natural cooling, the catalyst at the bottom of the reactor was centrifugally washed with CH3OH three times to obtain a white powder. The obtained white powder was then placed in a vacuum oven at 60 ° C and dried overnight, and the final powder obtained was Ni / ZIF-8.

[0033] Comparative Example 2

[0034] Synthesis of porous metal-organic framework (M-ZIF-8) materials with different metal loadings

[0035] 0.1g ZIF-8 was dissolved in 35mL acetonitrile, ultrasonically treated for 5min, and then 5mL of acetonitrile solution of metal precursor solution (4mg, 5mL) was added to the suspension and stirred for 30min. The metal solutions were ferric chloride hexahydrate, copper chloride dihydrate, and cobalt chloride hexahydrate. By controlling the amount of loaded metal solution added, a metal precursor solution with a loading of 1% was obtained. Then, an acetonitrile solution of NaBH4 (6.8mg, 10mL) was dripped into the mixed solution. In order to complete the reaction, stirring was continued for 20min until no bubbles were generated. The precipitate was collected by centrifugation and washed with acetonitrile several times. Finally, it was dried in a vacuum oven at room temperature to obtain the finished product M-ZIF-8 (M=Fe, Cu, Co).

[0036] Experiments and data

[0037] The activity investigation method of photocatalytic CO2 reduction provided by the present invention is as follows:

[0038] The photocatalytic CO2 reduction reaction was carried out using a fully automatic online trace gas analysis system (Labsolar-6A). First, 4 mL of deionized water, 4 mL of triethanolamine (TEOA) and 12 mL of acetonitrile (MeCN) solution were added to a reactor (250 mL, with a quartz cover), followed by the addition of 5 mg of photocatalyst and 30 mg of [Ru(bpy)3]Cl2·6H2O. After stirring with a magnetic stirrer for 30 min, the mixed solution was ultrasonically mixed for 30 min to mix evenly. The reactor was installed at the air inlet of the reaction system, and then the reaction system was evacuated using a vacuum pump, and approximately 1 atm (25 mL) of CO2 (99.99%) gas was introduced through a flowmeter. In order to remove the air from the reaction system as much as possible, the above-mentioned gas washing process was repeated 3 times. Two sets of condensation water systems were used in this paper, in which 10°C condensation water was introduced into the inner wall of the reactor, and -3°C condensation water was used at the outlet of the reactor connected to Labsolar-6A to prevent water vapor from entering the 5A column of the chromatogram. Finally, the laboratory light source (300W xenon lamp, wavelength range of light is 400-780nm) was vertically irradiated through the quartz cover of the reactor. During the photocatalytic CO2 reduction reaction, the gas in the reactor was passed into the gas chromatograph (GC-9790Ⅱ) for detection every 1 hour through Labsolar-6A. Carbon-containing products such as CH4, CO, CH3OH, and multi-carbon products were analyzed by flame ionization detector (FID), and other H2, O2, and N2 were detected by thermal conductivity detector (TCD).

Claims

1. A method for preparing nickel cluster-loaded porous metal organic framework materials for photocatalytic reduction of carbon dioxide, Features ZIF-8 was first prepared as a carrier by a hydrothermal method, and then a metal precursor solution and sodium borohydride in acetonitrile were added for reduction to obtain a porous metal-organic framework hybrid material with highly dispersed nickel clusters. The prepared material has excellent carbon dioxide capture, light energy utilization and charge separation capabilities, and can exhibit good photocatalytic carbon dioxide reduction performance; specifically, the following steps are included: Step 1: Zn(NO 3 ) 2 6H 2 O (1.116 g) dissolved in CH 3 OH (30 mL) solution and ultrasonically treated for 3 min to form solution A; then dimethylimidazole (1.232 g) was dissolved in CH 3 OH (30 mL) solution, ultrasonically treated for 3 min to form solution B; then, solution A and B were mixed and ultrasonically treated for 10 min, the mixed solution was poured into a 100 mL polytetrafluoroethylene reactor, and then reacted in a 120 °C constant temperature oven for 2 h; after natural cooling, the catalyst at the bottom of the reactor was quenched with CH 3 OH was centrifuged and washed three times to obtain a white powder; the obtained white powder was then placed in a vacuum oven at 60 °C and dried overnight, and the final powder obtained was ZIF-8; Step 2: 0.1 g ZIF-8 was dissolved in 35 mL acetonitrile and ultrasonicated for 5 min. Then 5 mL NiCl 2 6H 2 O (4 mg, 5 mL) in acetonitrile was added to the suspension and stirred for 30 min. NaBH 4 acetonitrile solution (6.8 mg, 10 mL); in order to complete the reaction, continue stirring for 20 min until no bubbles are generated; collect the precipitate by centrifugation and wash it with acetonitrile several times; finally, dry it in an oven under vacuum at room temperature to obtain the finished product Ni-ZIF-8; use a similar method to adjust the NiCl added during the reaction in proportion 2 6H 2 O and NaBH 4 The amount of 0.5Ni-ZIF-8 and 2Ni-ZIF-8 samples can be prepared; Step 3: Prepare porous metal organic framework materials loaded with other elements according to the methods of the first two steps, and replace nickel chloride hexahydrate with ferric chloride hexahydrate, cupric chloride dihydrate, cobalt chloride hexahydrate, and nickel nitrate hexahydrate respectively.

2. The method for preparing the nickel cluster-loaded porous metal organic framework material according to claim 1, Features: In the first step, the mixed solution was ultrasonically treated for 10 min until the transparent solution turned into a milky white solution to obtain a ZIF-8 precursor solution.

3. The method for preparing the nickel cluster-loaded porous metal organic framework material according to claim 1, Features: The NaBH prepared in step 2 4 The acetonitrile solution should be stored in a refrigerator.

4. The method for preparing the nickel cluster-loaded porous metal organic framework material according to claim 1, Features: In the second step, NaBH 4 The acetonitrile solution must be slowly dripped into the mixed solution, with bubbles generated and no obvious color change, in order to achieve complete reduction without contamination.

5. The method for preparing the nickel cluster-loaded porous metal organic framework material according to claim 1, Features: In the third step, by controlling the amount of NiCl added 2 6H 2 O and NaBH 4 Different loading amounts of Ni-ZIF-8 can be obtained by using the amount of Ni, and the mass fraction of Ni is controlled at 0.5%, 1%, and 2%. 2 6H 2 O dosages were 20 mg, 40 mg, and 80 mg, respectively, and the corresponding NaBH 4 The dosages were 34 mg, 68 mg and 136 mg respectively.

6. The method for preparing the nickel cluster-loaded porous metal organic framework material according to claim 1, Features: In the third step, the amount of other metal precursor solutions added was converted according to the mass fraction of the loaded metal to obtain samples with a metal loading of 1%.

Citation Information

Patent Citations

  • Preparation method of monatomic ruthenium doped-porous titanium-silicon material for efficient photocatalytic methane dry reforming

    CN115212875A

  • Perylene-based polymer loaded Ni monatomic photocatalytic material as well as preparation method and application thereof

    CN115845918A